Natural light vs artificial light. Effects of light pollution on the bioluminescence of dinoflagellate Pyrocystis lunula - Di Bari, Davide (2024)
Although there are thousands of marine bioluminescent species, very little is known about the effects of artificial light at night (ALAN) on these organisms, particularly those living near the sea surface, such as dinoflagellates. These organisms have a circadian clock that influences their rhythmic physiology, including processes like photosynthesis and nitrogen metabolism, which help regulate marine carbon and nitrogen cycles, respectively. The purpose of this study is to partially address this knowledge gap and research the effects of light pollution on the bioluminescent dinoflagellate Pyrocystis lunula through a series of experiments aimed at verifying the consequences due to changes in the normal day-night circadian cycle and exposure to different types of light source, colors, and light intensities. The response variable was the Corrected Total Algal Bioluminescence, which was recorded with a digital camera and then calculated with the ImageJ software. Results show that dinoflagellates do not appear to be susceptible to slight changes in the light/dark cycle. However, a total absence of light and darkness leads to a drastic inhibition of their bioluminescence, particularly under white LED or incandescent artificial light and with a light intensity of 100 lux or higher.